IMPLEMENTASI BUDAYA SEKOLAH DALAM MEMBENTUK KARAKTER RELIGIUS PESERTA DIDIK DI SD NO. 6 BELOK KECAMATAN PETANG KABUPATEN BADUNG (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
Abstract: School are place where formal education take place, school are not only place for teacher to diliver various subject, but school al also institution for forming character. A fenomenon in SD No. 6 Belok is suspected ofapplying school culture is shaping the character of student so that it is worthy of research. The formulation of the problem discussed there are 3, namely 1) what is the form of implementation of school culture in shaping the religious character of student in SD No. 6 Belok Petang District Badung regency? 2) What efforts are made in shaping the religious character of the student in SD No. 6 Belok Petang Distric Badung Regency? 3) what the impact of implementation school culture in shaping the religious character of student in SD No. 6 Belok Petang District Badung Regency?. The theory used is 1) the theory of behaviorism, 2) The theory of otivation. This type of research uses a qualitative descriptive approach. Method of collecting data by observation, interview, documentation nd literature study. The informant identification techniques is porposive sampling. Techniquesfor checking data validity are 1) credibility, transferability, dependability, confirmability. Data analysis whit 1) data reduction, 2) data display, 3 conclusion. The results of the study 1) The from of implementation of school cultur in shaping the character of student through habituation (1) carrying out prayers in class, (2) commemorating religious holidays, (3) 5S culture, (4) honest culture, (5) friendship culture, (6) culture of tolerance, (7) culture of literacy, (8) culture of carrying out flag ceremonies, (9) culture of caring for the school environment, (10) extracurricular. 2) The efforts made in shaping the religious character of student through 3 efforts (1) the efforts of the principal, (2) the efforts of the teacher, (3) the efforts of the student. 3) The impact of implementation school culture in shaping the religious character of student (1) impact on student, (2) impact on teacher, (3) impact on school, (4) impact on community environment.